Use of plant essential oils for the management of sheath blight disease in rice - Pal, Rini; Mandal, Dipankar (ORYZA-An International Journal of Rice, 2023)
Sheath blight caused by Rhizoctonia solani Kuhn is one of the most important diseases on the major high yielding rice varieties. Because of lack of resistant donor lines, no variety is completely immune to the disease. Till now, chemical control is the most widely used means to manage the disease which may have several adverse effects on the environment. Plant essential oils are among the most promising compounds for bio rational pest management. As highly volatile compounds are found in essential oils, they therefore cause no residue problems either in crop or in soil and are less subject to resistance. Keeping these factors in view, a field experiment was conducted at All India Co-Ordinated Rice Improvement Project, Chiplima, Sambalpur, Odisha during kharif and rabi seasons of 2019-20 and 2020-21 respectively to assess the effect of seven essential oils for the management of sheath blight disease in rice. They were sprayed twice at weekly interval starting from the third day of inoculation. Among all the essential oils, citronella oil @ 2ml l-1 was found best to manage the disease during both the years of experiment. It gave 36% disease control compared to check plots. Under invitro condition also, citronella oil @ 500 ppm proved to be the best of all the essential oils. Though the chemical check carbendazim gave the highest disease control (47.25%) but considering the environmental point of view, citronella oil @ 2ml l-1 can be recommended as an alternative to manage sheath blight disease in rice without any toxic effect on the crop.